Pengaruh Moralitas Individu dan Pengendalian Internal Terhadap Kecenderungan Kecurangan Akuntansi Dalam Pengelolaan Keuangan Badan Usaha Milik Daerah (BUMD) - Muhammad Agung Setiawan; Jeni Wardi (Jurnal Karya Ilmiah Multidisiplin (JURKIM), 2024)
This study aims to analyze the influence of individual morality and internal control on the tendency of accounting fraud in the financial management of Regional-Owned Enterprises (BUMD) in Siak Regency. Furthermore, it aims to analyze the influence of individual morality on the tendency of accounting fraud in the financial management of Regional-Owned Enterprises (BUMD) in Siak Regency. Additionally, it seeks to analyze the influence of internal control on the tendency of accounting fraud in the financial management of Regional-Owned Enterprises (BUMD) in Siak Regency. The sampling technique used is simple random sampling. The reason for using simple random sampling is because it is the easiest to apply, and every member of the population can be selected as a sample. Individual morality influences fraud prevention. Internal control affects fraud prevention. The research findings indicate that, simultaneously, individual morality and internal control have an impact on fraud prevention. Future researchers can expand the research object by giving more consideration to caution when generalizing the research object.